Keeping the memory of Napoleonic wars: forms of international cooperation between Russia and the German Empire at the beginning of the twentieth century - A. S. Lizogub (Омский научный вестник: Серия "Общество. История. Современность")
The article is devoted to the characteristics of the main forms of international cooperation used at the beginning of the twentieth century keeping the memory of significant events in military history. Based on archival documents, press materials and personal testimonies, the preparation, semantic content and attitude of society towards Russia’s participation in commemorative projects implemented on the territory of the German Empire on the eve of the First World War are analyzed. The focus is on considering the features and problems of building narratives about the joint military past of the two empires within the framework of the international exhibition in Breslau and the opening of monuments in Leipzig. The author concluded that the implementation of commemorative projects dedicated to the 100th anniversary of the victory in the Napoleonic wars is influenced by the existing system of international relations. Behind the scenes of the grandiose celebrations was hidden the desire of the German Empire to provide a historical justification for its foreign policy course. For the Russian state, participation in joint projects provided an opportunity to remind Europe of its role in the international arena and the strength of the army. Promising directions for further research of the problem are outlined.